Right Ventricular Wall Motion and Performance in Stabilized Chronic Respiratory Failure Evaluated by Equilibrium Radionuclide Angiocardiography - Maini, C. L.; Incalzi, R. Antonelli; Bonetti, M. G.; Fuso, L.; Valle, G. (Nuklearmedizin - NuclearMedicine, 1986)
Equilibrium radionuclide angiocardiography (ERNA) was performed at rest in 30 patients with chronic respiratory failure (CRF) in order to evaluate right ventricular performance and wall motion. The usual indices of left ventricular performance were also recorded and correlated with right ventricular parameters. Only CRF patients without clinical, electrocardiographic or echocardiographic criteria suggestive of congenital, valvular, hypertensive or ischemic heart disease were studied. A RV dyskinesis was detected in 5 of the 30 patients, occurring however only in stage II—III CRF, as if a longstanding RV pressure overload were necessary for a RV dyskinesis to develop. No significant differences were found between patients with and without RV dyskinesis for all the functional ERNA parameters (i.e. LVEF, RVEF, PER, PFR) On the other hand, a significant correlation between the stage of the CRF and RVEF was observed.